ASSESSMENT OF LAND COVER CHANGES AND THE CAUSES OF MANGROVE DEGRADATION IN PYINDAYE RESERVED FOREST, AYEYARWADY DELTA, MYANMAR TOWARD SUSTAINABLE MANGROVE MANAGEMENT TO MITIGATE THE CONSEQUENCES OF CLIMATE CHANGE - Xuan Truong, Le; Naing Phyo, Yan; Viet Ha, Tran; Minh Thanh, Nguyen; Thi Mai Sen, Tran (Journal of Forestry Science and Technology, 2019)
This study analyzed the land use changes during 2000 - 2019 by using multi-temporal landsat of unsupervised classification and the influencing factors on the key drivers of mangrove degradation especially fuel wood consumption and aquaculture areas expansion in the study area. This study employed both qualitative and quantitative methods including interviews with 118 participants through questionnaire surveys and focus group discussion. The results revealed both increase and decrease of different land cover change (LCC) from 2000 through 2019. Significant shifts from some classes to other was also observed. Drivers of the observed changes ranged from climatic factors such as natural disasters to socio-economic factors. Regression analysis results showed that the key drivers of mangrove degradation especially fuel wood consumption and aquaculture areas expansion have strongly and positively significant influenced on the mangrove degradation. Aquaculture was a cause of loss of mangrove areas in Ayeyarwady Delta including the study areas due to overexploitation to develop the commercial shrimp farms. Thus, mangrove degradation is one of the most important environmental problems that the government needs to address and set up the policy, rules and regulations in order to mitigate the consequences of Climate Change in this area.